The Influence of Perceived Ease of Use, Risk And Financial Ability on Transaction Interest In Using Tiktok Paylater on Students In Sukabumi City - Aliya Nurfauzia; Dicky Jhoansyah; R. Deni Muhammad Danial (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine the effect of perceived ease of use, risk, financial ability on transaction interest, the temporary assumption is that the three variables have a significant effect on transaction interest using Tiktok Paylater, this study uses a quantitative method with an associative descriptive approach, with a sample size of 225 samples, the sampling technique uses purposive sampling. Data collection through questionnaires and literature studies. The results of the f test statistics show a simultaneous and significant effect of the variables perceived ease of use, risk and financial ability on transaction interest. Based on the results of the t test statistics, perceived ease of use does not have a significant effect on transaction interest with the t test (0.184> 0.05). In the variable, risk has a significant effect on transaction interest with the test results (0.000 <0.05). While financial ability has a positive and significant effect on transaction interest with the t test (0.000 <0.05). The implications of this study can be used as a basis for increasing interest in transactions using Tiktok Paylater through perceived ease of use, risk, financial ability among students in Sukabumi City.